UPAYA MENINGKATKAN KREATIVITAS SISWA MELALUI PENERAPAN MODEL MIND MAPPING DALAM PEMBELAJARAN FIKIH - Rika Deswanti (BRIGHT VISION Journal of Language and Education, 2022)
This study aims to describe efforts to increase student creativity through the application of Mind Mapping models in fiqh learning at MIN 3 Kota Medan. This research uses a qualitative approach with a descriptive study method. Observation, interview, and document study techniques are three research data acquisition techniques. Then, the data were analyzed using an interactive analysis model, through the steps of data collection, data sorting, data presentation, and drawing conclusions. The results of this study indicate that the application of the Mind Mapping model makes it easier for educators in the thematic learning process, because it stimulates students to develop their creativity based on the spirit of group learning. Likewise, there are obstacles in the implementation of the learning model, namely the low focus of students in group activities, the teacher's difficulty controlling student learning behavior, and there are some students who like to disturb their friends.